The Effect of Price and Taste on The Purchase - Rahmat hidayat; Intisari Haryanti (Almana : Jurnal Manajemen dan Bisnis, 2020)
Many business people who open a culinary business as a human need that serves fast food and drinks. Based on the habit of these people who prefer to buy fast food and drinks, it will benefit these business people, one of which is a culinary or restaurant business. Ranging from snacks to heavy food. Consisting of regional food, and even Korean food. Competition between culinary businesses is increasingly high. Aisy Drink is one of the hundreds of culinary businesses that sell fast food and beverages. Many menu choices provided, such as fried rice, noodles, and kebabs. Likewise, the drink, there are many choices of flavors. By carrying out the theme of hospitality, this place is a favorite choice of youth and other circles. However, buyers are increasingly here increasingly quiet. The results of observations by researchers with other similar businesses, the price in Aisy Drink is quite expensive, both food and drinks. The food was pegged at a price above twenty thousand, while the drinks were in the range of fifteen thousand rupiahs. The researcher is interested in researching this matter and the researcher hopes that this research can become an example for other prospective entrepreneurs, especially graduates from STIE Bima.